Osteosarcoma: a fluid cytologic diagnosis - T., Mitila; Priya Asokan, Lakshmi; Chander, Vimal (International Journal of Research in Medical Sciences, 2023)
Osteosarcoma is the most common malignant bone tumor characterized by the formation of disorganized immature bone or osteoid tissue from mesenchymal tumor cells. It most commonly occurs in the appendicular skeleton involving the metaphysis of long bones. It is the third most common cancer in adolescence with an annual incidence of 5.6 cases per million children under the age of 15 years. Giant cell-rich osteosarcoma (GCRO) is an exceedingly rare histological variant of conventional primary osteosarcoma. It constitutes about 1%-3% of all osteosarcomas. A 20-year-old male presented with the complaints of pain and swelling over the right knee. Examination revealed a tender 15×10×8 cm swelling palpable on the distal femur. Radiological investigations showed features suggesting right femoral osteosarcoma in the meta-epiphyseal region. A core needle biopsy from the lesion was performed and 15 ml of fluid obtained from the biopsy site was sent for cytological examination, which showed features suggestive of osteosarcoma. Biopsy showed features of osteosarcoma probably of giant cell rich type confirming the fluid cytology findings. Cell block preparation also revealed giant cell predominance. Osteosarcoma is a bone tumor found in areas of rapid bone turnover, most commonly the distal femur and proximal tibia of adolescent patients. Cytology plays a vital role in diagnosing bone tumors, being a rapid, easy, and minimally invasive outpatient department procedure. Histopathology, since it gives a complete architectural pattern of tissue, remains the gold standard diagnostic tool.